1997
DOI: 10.1002/jsl.3000140202
|View full text |Cite
|
Sign up to set email alerts
|

Miscibility and stability of synthetic lubricants with HFC refrigerants

Abstract: The phase-out of CFC production and further regulations on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In refrigeration, highly soluble lubricants are required for adequate lubricant return and to prevent fouling of the capillary tube and evaporator. 12 Very lipophilic hydrocarbon lubricants are generally highly miscible in CFCs and HCFCs. The same lubricants, however, are generally not compatible with the more polar HFAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In refrigeration, highly soluble lubricants are required for adequate lubricant return and to prevent fouling of the capillary tube and evaporator. 12 Very lipophilic hydrocarbon lubricants are generally highly miscible in CFCs and HCFCs. The same lubricants, however, are generally not compatible with the more polar HFAs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the transition from CFCs and HCFCs to the more environmentally friendly HFAs has been somewhat problematic due in large extent to the significantly different solvent properties between these classes of fluids. In refrigeration, highly soluble lubricants are required for adequate lubricant return and to prevent fouling of the capillary tube and evaporator . Very lipophilic hydrocarbon lubricants are generally highly miscible in CFCs and HCFCs.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the stability of POEs and PAGs deteriorates with the presence of moisture (Wu, and Thomas, 1997). The POEs undergo a hydrolysis process, which is opposite to the esterification.…”
Section: Visual and Chemical Changes Are Possible Through The Chemicamentioning
confidence: 99%
“…POEs, manufactured with a higher percentage of branched acids, are more stable in the presence of water than those with a high proportion of linear acids. Wu, and Thomas (1997) reported that air as the contaminant usually has only a small effect on the stability of POEs. Contaminant metals, such as tin, must be avoided in refrigeration systems, since it is a catalyst for a chemical reaction between the refrigerant and lubricant.…”
Section: Visual and Chemical Changes Are Possible Through The Chemicamentioning
confidence: 99%